2022
DOI: 10.1021/acs.chemmater.2c02981
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Controlled Phase Separation of Liquid Metal-Based Eutectic Ternary Alloys

Abstract: Liquid metals (LMs) are immiscible in many common electrolytic solutions and, when immersed in them, establish phase boundaries that display intriguing interfacial characteristics. The application of a cathodic potential to such interfaces may trigger phase separation of solute elements out of the LMs. Here, we investigate this possibility in two of the most researched and industrially used eutectic ternary LMs of Galinstan (Ga-In-Sn) and Field’s metal (FM, In–Bi–Sn). We observe that upon surface perturbation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…5e–g). 8 Moreover, the interfacial crystal formation within metallic liquid–solid coexisting systems leads to unique growth dynamics, crystal structures and arrangements that are distinct from traditional solvent precipitation (Fig. 5h).…”
Section: Liquid Metal Reactors For Nanomaterials Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…5e–g). 8 Moreover, the interfacial crystal formation within metallic liquid–solid coexisting systems leads to unique growth dynamics, crystal structures and arrangements that are distinct from traditional solvent precipitation (Fig. 5h).…”
Section: Liquid Metal Reactors For Nanomaterials Synthesismentioning
confidence: 99%
“…6,7 Consequently, various metal elements can dissolve, precipitate, diffuse mutually and form intermetallic compounds within the LM matrix, making them ideal reaction media for materials synthesis. [8][9][10][11] Significantly, Ga features a low standard reduction potential (E 0 [Ga 3+ /Ga 0 ] = −0.529 V vs. the standard hydrogen electrode (SHE)), endowing it with a highly active surface for catalytic or reduction interface reactions. 12,13 More interestingly, LMs spontaneously form an ultra-thin oxide layer when exposed to air.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing an excess of Bi into liquid Ga metals can create a peculiar dynamic equilibrium, resulting in intriguing phenomena such as nucleation and local ordering of Bi elements. [9] Following the Bi─Ga phase diagram, our primary strategy involves alloying Bi and Ga at 350 °C (Bi: 2.5% and Ga: 97.5% weight percentage). [31] Accordingly, Bi at the chosen concentration is a dissolved element in liquid Ga, forming a homogeneous alloy at 350 °C.…”
Section: Nanoparticles Synthesismentioning
confidence: 99%
“…[8] In contrast, when segregation occurs via the application of an external electric field while the alloy is still liquid, it is possible to directly and completely expel nanoscale solute metals from the alloy, a process known as "metal expulsion." [9] Our recent research has demonstrated that electrochemistry can induce direct metal expulsion from liquid alloys using interfacial perturbations. [10] When liquid alloys are submerged in electrolytes, a liquid-liquid interface with distinct physical and chemical characteristics is formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation